Occupation Growth, Skill Prices, and Wage Inequality - Böhm, Michael J.; von Gaudecker, Hans-Martin; Schran, Felix (Journal of Labor Economics, 2024)
We study the relationship among occupational employment, occupational wages, and wage inequality. In all occupations, entrants and leavers earn less than stayers, suggesting negative selection effects for growing occupations and positive effects for shrinking ones. We estimate a model of occupational prices and skills that includes specific skill accumulation and endogenous switching. Contrary to uncorrected wages, prices and employment growth are positively related. Forty percent of selection is due to age, as entrants and leavers have had less time to accumulate skills. The remainder is Roy-type selection. Skill prices establish a quantitative connection of occupational changes with surging wage inequality.